2019
DOI: 10.1002/celc.201901113
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Si@Void@Graphene Anodes for Lithium‐Ion Batteries: InSitu Enveloping of Nickel‐Coated Silicon Particles with Graphene

Abstract: In this report, a yolk‐shell‐structured Si/graphene (Si/GR) material has been designed and successfully fabricated as an anode for lithium‐ion batteries (LIBs). With this approach, Si@Ni composite particles were fabricated by electroless deposition of a nickel template directly on silicon; then, three‐dimensional (3D) graphene layers were grown in situ around the composite particles to obtain a Si@Ni@GR structure. After removing the nickel interlayer, some voids were generated between the silicon particles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…VCrGO@Si-1 retained around 80.6 % of the initial capacity after 200 cycles while VCrGO@Si-0 only retained 61.3 %. At a higher active material loading of 2.4 mg cm À 2 , VCrGO@Si-1 displayed a high areal capacity of 2.26 mAh cm À 2 , which only dropped by < 20 % after [20,23,24,26,33,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] 145 cycles. Based on the calculation for the capacity contributed by pure silicon (94.3 %) at 1 A g À 1 , the carefully tuned reserved void space of VCrGO@Si-1 can effectively buffer the volume change of Si NPs in the core, without introducing excess volume, improving overall performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VCrGO@Si-1 retained around 80.6 % of the initial capacity after 200 cycles while VCrGO@Si-0 only retained 61.3 %. At a higher active material loading of 2.4 mg cm À 2 , VCrGO@Si-1 displayed a high areal capacity of 2.26 mAh cm À 2 , which only dropped by < 20 % after [20,23,24,26,33,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] 145 cycles. Based on the calculation for the capacity contributed by pure silicon (94.3 %) at 1 A g À 1 , the carefully tuned reserved void space of VCrGO@Si-1 can effectively buffer the volume change of Si NPs in the core, without introducing excess volume, improving overall performance.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7. Areal capacity retention of recent works reporting Si/C based anode [20,23,24,26,33,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. …”
mentioning
confidence: 99%
“…involved electrochemical deposition to coat nickel template on the surface of clusters of Si nanoparticles, then graphene was formed in situ through the catalysis of Ni on triethylene glycol, and Ni template was removed by HF solution to get Si@void@GR composite (Figure 8A). [ 126 ] TEM images showed that several Si nanoparticles were surrounded by a complete graphene layer with void around (Figure 8B). Compared with bare Si, Si@void@GR showed significantly improved cycle and rate performance (Figure 8C).…”
Section: Contact Engineeringmentioning
confidence: 99%
“…C, Rate capabilities of Si and Si@void@GR at current densities ranging from 0.5 to 4.8 Ag –1 . [ 126 ] Copyright 2019, Wiley‐VCH. D, TEM image of the SiNPs@C PS composite with schematic inset.…”
Section: Contact Engineeringmentioning
confidence: 99%
“…Ni catalyst was etched away by FeCl 3 aqueous solution and was thought as a sacrificial layer for providing void space for Si microparticles expansion within the graphene cage. Zhao et al [28] designed a yolk-shell-structured Si/ graphene material as an anode for lithiumion batteries, which showed a high reversible discharge capacity of 1595 mAh g −1 after 100 cycles at a current density of 500 mA g −1 and 990 mAh g −1 at a higher current density of 4.8 A g −1 . Herein, lithium-ion transport efficiency and electron transport rate may be enhanced by the graphene cover, causing the improvement of the anodic electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%